Potent Imidazothiazole-based Inhibitor of BRAF V600E Overcomes Acquired Resistance via Inhibition of RAF Dimerization in PLX4032-resistant Melanoma - Poudel, Muna; Kim, Garam; Bhattarai, Poshan Yugal; Shin, Seung; Zaraei, Seyed-Omar; Oh, Chang-Hyun; Choi, Hong Seok (International Institute of Anticancer Research, 2022)
Background/Aim: The B- raf proto-oncogene, serine/threonine kinase (BRAF) V600E mutation is frequent in patients with advanced melanoma. PLX4032, an inhibitor of BRAFV600E kinase, is effective for the treatment of melanoma in BRAF V600E-positive patients; however, resistance eventually develops due to paradoxical activation of the mitogen-activated protein kinase kinase (MEK)/extracellular signal- regulated kinases (ERK) pathway resulting from RAF dimerization. In this study, we investigated the inhibitory effects of a novel imidazothiazole-based compound, KS28, on RAF dimerization and resistance to PLX4032 in melanoma. Materials and Methods: The effects of KS28 were examined by immunoblotting, cell viability, terminal deoxynucleotidyl transferase dUTP nickend labeling, reporter-gene, and soft- agar assays. Results: KS28 treatment inhibited RAF dimerization in PLX4032resistant A375 (A375R) cells, leading to suppression of the MEK/ERK pathway. In addition, KS28 reduced activator protein 1 transactivation in A375R cells, reduced cell viability, and increased DNA fragmentation. Moreover, treatment with KS28 suppressed anchorage-independent growth of A375R cells. Similarly, in an orthotopic tumor xenograft model, KS28 treatment suppressed the growth of tumors formed by A375R cells in BALB/c mice. Conclusion: KS28 plays a vital role in overcoming PLX4032 resistance in melanoma by down- regulating the MEK/ERK pathway.